RESPONS KEBIJAKAN PEMERINTAH DAERAH DALAM PEMANFAATAN ANGGARAN DID PADA PERIODE AWAL PANDEMI COVID-19 - Andi Setyo Pambudi (Jurnal Kebijakan Pembangunan Daerah, 2023)
During the COVID-19 Pandemic, transfer funds were significant in helping the regions respond to the situation. The use of transfer funds, especially the Regional Incentive Fund (RIF), is interesting to study, considering that regions applied creativity at the beginning of the COVID-19 pandemic in various ways. This study aims to obtain information on different regional reactions to the utilization of the RIF budget in the early period of the COVID-19 pandemic, to find out the development problems funded by the RIF from the regions with the best Regional Development Awards (RDA), and to obtain input for more adaptive RIF planning. The research method used is descriptive quantitative with data collection techniques through focus group discussions (FGDs with participants from each of the three Provincial, City, and Regency Development Planning Agencies that won the Regional Development Award/RDA) in 2020. The analysis used a combination of literature. The results showed that RIF in the early period of the COVID-19 pandemic provided significant benefits for the regions in policies that adapted to the local situation of development in the health sector and economic recovery. Furthermore, this research find that the field implementation of RIF had not been comprehensively successful in promoting regional independence in general, the regions late received information on the budget ceiling, and the diverse regional characteristics and the availability of resources are fundamental factors in achieving quality spending.